Multiple Protein Disulfide Isomerases support Thrombosis - Essex, David (Curr Opin Hematol, 2018)
PURPOSE OF REVIEW: This review provides an overview of recent findings on new members of the protein disulfide isomerase (PDI) family required for thrombosis. RECENT FINDINGS: Twenty years ago PDI was shown to mediate platelet aggregation, and ten years ago PDI was shown to support thrombosis in vivo. Subsequently, other members of this endoplasmic reticulum family of enzymes, ERp57 and ERp5, were demonstrated to support thrombosis. A fourth member, ERp72, was recently shown to be required for platelet accumulation and fibrin deposition in vivo. None of these enzymes can individually support these processes. Moreover, aggregation of platelets deficient in a specific PDI is only recovered by the PDI that is missing. This implies that each PDI has a distinct role in activation of the αIIbβ3 fibrinogen receptor and platelet aggregation. Free thiols can be labeled in both subunits of αIIbβ3 suggesting cysteine-based reactions are involved in relaying conformational changes from the cytoplasmic tails to the integrin headpiece of this integrin. SUMMARY: Multiple members of the PDI family support platelet function, and hemostasis and thrombosis with distinct roles in these processes. The individual cysteine targets of each enzyme and how these enzymes are integrated into a network that supports hemostasis and thrombosis remain to be elucidated.